2020
DOI: 10.5194/acp-20-13781-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ozone affected by a succession of four landfall typhoons in the Yangtze River Delta, China: major processes and health impacts

Abstract: Abstract. Landfall typhoons can significantly affect O3 in the Yangtze River Delta (YRD) region. In this study, we investigate a unique case characterized by two multiday regional O3 pollution episodes related to four successive landfall typhoons in the summer of 2018 in the YRD. The results show that O3 pollution episodes mainly occurred during the period from the end of a typhoon to the arrival of the next typhoon. The time when a typhoon reached the 24 h warning line and the time when the typhoon dies away … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…Figure 3 further shows monthly MDA8 O 3 in the 26 cities in the YRD from 2015 to 2019, the monthly MDA8 O 3 in most cities over the YRD reaches its maximum in May or June, and then O 3 concentration slowly decreases due to Asian summer monsoon (He et al., 2008; Hou et al., 2014; Zhou et al., 2013). Around early autumn, MDA8 O 3 in some cities can reach a second peak, which may be related to typhoon activities (Shu et al., 2016; Zhan et al., 2020). In general, high O 3 concentration in the YRD tends to appear in warm seasons (April‐September), which is consistent with the result of TCO (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 further shows monthly MDA8 O 3 in the 26 cities in the YRD from 2015 to 2019, the monthly MDA8 O 3 in most cities over the YRD reaches its maximum in May or June, and then O 3 concentration slowly decreases due to Asian summer monsoon (He et al., 2008; Hou et al., 2014; Zhou et al., 2013). Around early autumn, MDA8 O 3 in some cities can reach a second peak, which may be related to typhoon activities (Shu et al., 2016; Zhan et al., 2020). In general, high O 3 concentration in the YRD tends to appear in warm seasons (April‐September), which is consistent with the result of TCO (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhan et al. (2020) found that synoptic systems, such as typhoons, can largely impact O 3 pollution episodes. However, these studies only focused on individual stations or a couple of representative cases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that surface ozone concentrations in PRD and YRD are enhanced when typhoons are 700-1000 km away and when typhoons cross the 24-h warning line (thick black dashed line in Fig. 1) (e.g., Huang et al, 2006;Zhan et al, 2020). In addition to these valuable findings of ozone enhancement over the developed regions, this paper examines the overall surface ozone behaviours associated with landfalling typhoons over southern China, and comprehensively addresses both positive and negative impacts of typhoons on surface ozone concentrations in the following part.…”
Section: Reanalysis Meteorological Datamentioning
confidence: 87%
“…It is also documented that surface ozone concentrations increase over southwestern Taiwan 2 to 4 days before the passage of typhoons (Hung and Lo, 2015). Recently, Zhan et al (2020) found that in YRD ozone pollution episodes mainly occurred when a typhoon reaches the 24-h warning line (thick dashed line in Fig. 1) and the previous typhoon dies away in mainland China.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation